Pengaruh Model Pembelajaran Kooperatif Tipe Artikulasi yang Disertai LKS terhadap Hasil Belajar Siswa Biologi Kelas XI MIA SMA Negeri 1 Kota Solok - Yola Gustia Sari; Afrahamiryano Afrahamiryano; Darmanella Dian Eka Wati (Pendidikan Biologi FKIP UMMY, 2020)
The low learning outcomes Biology of second grade MIA SMA Negeri 1 Kota Solok requires teachers to look for alternatives to increase student learning outcomes by creating a warm learning atmosphere between students and teachers so that good communication. One of- the ways that can be used is the Cooperative Learning Model Articulation with Student Worksheet (LKS). The problem of this research is